If it's not what You are looking for type in the equation solver your own equation and let us solve it.
x in (-oo:+oo)
(2/3)*x+12 = 2*x+6 // - 2*x+6
(2/3)*x-(2*x)-6+12 = 0
(2/3)*x-2*x-6+12 = 0
6-4/3*x = 0 // - 6
-4/3*x = -6 // : -4/3
x = -6/(-4/3)
x = 9/2
x = 9/2
| 2(2a-b)-8(3-5a)= | | X^9-9X^3+8=0 | | 4x(x+3)-7(x-3)=0 | | 3/8(4p+6)=1/12p-17 | | 1.3x=30643+x | | (x-1)/5+3(x+2)=x/2 | | 1.3x=4933+2000+x | | 4(3x+2)=-6 | | 11(x-3)=5x | | 4(3x+2)=-7 | | 9k-[7-5(7k-3)]= | | 2m+2=18 | | (-a-3b+2)3ab= | | -19=3t+-4 | | 3x/4+2=-1 | | .5x=100 | | 1.3x=1600+x | | t/4+11=13 | | 140=10x-8x | | -2=4y-10 | | 2h+-3=3 | | 1+2h=7 | | 3z+3=6 | | 6=2b+2 | | 6=2b+1 | | 3c-2=1 | | 12/10=y+6/13 | | g/6+12=17 | | 11=j/7+17 | | 12+-7h=-9 | | 5+4(x-2)=2(t+7)+1 | | s/2+7=9 |